(untitled) (AYUSHDHARA, 2023)
The arenas of reproductive and developmental toxicology are multifaceted areas of significant importance and intense study, for the human population, as well as for animal species. Due to impact from various toxicants, from pharmaceuticals to environmental contaminants increases risks of adverse effects to Reproductive systems and developing embryos and foetuses. There is lots of information found in relation with environmental toxicants and their effects on reproductive system of male and female as well as on foetus. There is need of scientific Research about effects of toxicants on the process of reproduction and on developing foetus through molecular, physiological and anatomical studies including reversibility of their impacts. Also, studying fewer common exposures like new types of chemicals, occupational factors and exposure by inhalation. People may encounter substances that have harmful impact on reproductive health as well as developing embryo and foetus through water, air, soil, dust, food, or consumer products. The ultimate aim of all scientific toxicological research is to utilize unfailing and predictive toxicity testing to prevent exposure to potentially harmful toxicants on reproducing animals, humans as well as developing individuals. Also, study of role of the placenta in developmental toxicity of chemicals is essential.